2017
DOI: 10.1111/mmi.13867
|View full text |Cite
|
Sign up to set email alerts
|

Post‐translational modifications as key regulators of apicomplexan biology: insights from proteome‐wide studies

Abstract: Summary Parasites of the Apicomplexa phylum, such as Plasmodium spp. and Toxoplasma gondii, undergo complex life cycles involving multiple stages with distinct biology and morphologies. Post‐translational modifications (PTMs), such as phosphorylation, acetylation and glycosylation, regulate numerous cellular processes, playing a role in every aspect of cell biology. PTMs can occur on proteins at any time in their lifespan and through alterations of target protein activity, localization, protein–protein interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 204 publications
(366 reference statements)
0
50
0
Order By: Relevance
“…During the regulation of several key biological processes, protein post-translational modifications (PTMs), such as acylation, phosphorylation, and methylation, reversibly modify specific amino acid residues and play important roles in maintaining diverse cellular processes and functions [1,2]. Of these PTM sites, lysine is the most commonly modified amino acid residue, with only a single ionic interaction formed, thus offering more functional flexibility following acetylation, methylation, or ubiquitination [3].…”
Section: Introductionmentioning
confidence: 99%
“…During the regulation of several key biological processes, protein post-translational modifications (PTMs), such as acylation, phosphorylation, and methylation, reversibly modify specific amino acid residues and play important roles in maintaining diverse cellular processes and functions [1,2]. Of these PTM sites, lysine is the most commonly modified amino acid residue, with only a single ionic interaction formed, thus offering more functional flexibility following acetylation, methylation, or ubiquitination [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, post-translational modifications (PTMs) of proteins, and glycosylation, are of considerable interest, because polysaccharides are known as being recognized by the immune system. In Plasmodium parasites, several PTMs were detected (reviewed in (123)(124)(125)) and the generation of antibodies recognizing glycosylated proteins during natural exposure has been described earlier (126,127). Recent work shed more light into N-and O-glycosylation in malarial parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression-subtractive hybridization ( Peng et al, 2016 ) and transcriptomic studies ( Long et al, 2013 ; Chopra et al, 2015 ; Wang et al, 2015 ) of shrimp and zebrafish have been carried out to better understand the molecular mechanisms involved in cold tolerance in aquatic organisms. Recently, proteomic techniques were extensively used in research associated with human disease ( Zhu et al, 2018 ), protein o-glycosylation ( You et al, 2018 ), and apicomplexan biology ( Yakubu et al, 2018 ). Little is known about the proteome of Pacific white shrimp ( Lu et al, 2016 ), especially under cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses found that the expression levels of several DAPPUDRAFT proteins (240262, 307838, and 206907) were higher in GH2 than in GH1, suggesting that the cold tolerance of GH2 was related to alkaline phosphatase activity, most likely due to the fact that these enzymes can help protect the liver, bones, and blood of shrimp from cold-stress damage. Interestingly, not all the cold-responsive gene expressions that procede protein synthesis, and this could be due to a lack of energy for modification at post-transcriptional and post-translational levels, such as glycosylation ( Yakubu et al, 2018 ; You et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%